Hierarchically self-assembled semiconducting and polysaccharide nanocrystals with multiscale chirality - Hong, Jai; Choi, Yujeong; Kwon, Junyoung (Frontiers in Materials, 2025)
Hierarchically chiral structures exhibit multiscale chirality across multiple length scales, ranging from the atomic to the micrometer scale. Recent studies have investigated their pronounced circular dichroism (CD) signals, chemical stability, and new properties, demonstrating their potential for diverse applications. This review focuses on the characteristics of semiconductor and polysaccharide nanocrystals that exhibit hierarchical architectures with two or more levels, with structural features ranging from 0.1 nm to 10 nm, 1 μm, and up to 10 μm. Particular attention is paid to small nanoparticles such as Cu2S and CdTe in the category of semiconductors, and to cellulose and chitin nanocrystals among organic nanocrystals. Chiral semiconducting nanocrystals exhibit distinctive characteristics, including remarkable self-assembly capabilities into hierarchical structures and corresponding optical activities. Polysaccharide nanocrystals such as cellulose nanocrystals can be self-assembled into a chiral nematic liquid crystal phase, exhibiting strong chiral light reflection. This review provides a brief overview of recent studies of hierarchically chiral nanomaterials and their potential applications in optoelectronic devices, tunable color films, and optical sensors. This will facilitate a deeper understanding of underlying mechanisms and functional properties of hierarchically self-assembled chiral nanomaterials.